Regional subsidies and industrial prospects of lagging regions - Lall, Somik V., 1972- 1972- (Policy research working paper, 2006)
"Large and sustained differences in economic performance across regions of developing countries have long provided motivation for fiscal incentives designed to encourage firm entry in lagging areas. But empirical evidence in support of these policies has been weak at best. The authors undertake a direct evaluation of the most prominent fiscal incentive policy in Brazil, the Fundos Constitucionais de Financiamento (Constitutional Funds). In doing so, they exploit valuable features of the Brazilian Ministry of Labor's RAIS data set to address two important elements of firm location decisions that have the potential to bias an assessment of the funds: (1) firm "family structure" (in particular, proximity to headquarters for vertically integrated firms), and (2) unobserved spatial heterogeneity (with the potential to confound the effects of the funds). The authors find that the pull of firm headquarters is very strong relative to the constitutional funds for vertically integrated firms, but that, with nonparametric controls for time invariant spatial heterogeneity, the funds provide significant incentives for firms in many of the targeted industries. "--World Bank web site